Dopaminergic drugs alter beta coherence during motor imagery and motor execution in healthy adults - Danielle APRIGIO; Guaraci Ken TANAKA; Juliana BITTENCOURT; Mariana GONGORA; Silmar TEIXEIRA; Mauricio CAGY; Henning BUDDE; Marco ORSINI; Pedro RIBEIRO; Bruna VELASQUES (Arquivos de Neuro-Psiquiatria)
Abstract Background: Motor Imagery (MI) represents the cognitive component of the movement and recruits dopaminergic systems. Objective: To investigate the role of dopaminergic system through the action of methylphenidate and risperidone over beta coherence during execution, action observation and motor imagery. Methods: Electroencephalography (EEG) data were recorded before and after the substance intake. For statistical analysis, a three-way ANOVA was used to identify changes in beta coherence induced by the group, task and the moment variables. Statistical significance was set at p≤0.007. Results: We found a main effect for group for C3/CZ, and a main effect for task for CZ/C4 pairs of electrodes. Furthermore, significant differences were found in the post-drug administration between groups for C3/CZ pair of electrodes, and between task for C4/CZ pair of electrodes. Conclusion: The administration of methylphenidate and risperidone was able to produce electrocortical changes of the cortical central regions, even when featuring antagonistic effects on the dopaminergic pathways. Moreover, the execution task allowed beta-band modulation increase.